Transformation of Canine Lymphoma/Leukemia to More Aggressive Diseases: Anecdotes or Reality? - Comazzi, Stefano; Aresu, Luca; Marconato, Laura (Frontiers in Veterinary Science, 2015)
Transformation is the evolution of an indolent lymphoma/leukemia to an aggressive lymphoma, typically harboring a very poor prognosis. This phenomenon is well described in humans , but under-estimated in dogs although recognized as a possible evolution of indolent lymphomas/leukemias. In canine chronic leukemias blast crisis (mainly in myeloid ) and Richter syndrome (transformation into a high grade lymphoma) (mainly in B-cell lymphocytic leukemia) has been reported. Transformation is a possible event also in canine low grade lymphomas, although rare. The increased knowledge has also generated new questions and posed challenges that need to be addressed to improve outcome, including the recognition of the clinical characteristics at diagnosis associated with a higher risk of transformation in an attempt of anticipating the typical evolution.